Marriage and Lineage Segmentation in Ibibioland - Charles, J.O. (Anthropologica, 2022)
This article discusses the dynamics of Ibibio lineage structure. It presents ethnographic evidence that fission of maximal lineages (ekpuk) into minor lineages (ufok) in Ibibioland was principally a function of marriages involving agnatic kin. Such a marriage caused initial disruption in the lineage because it led to the creation of a new minor lineage with a separate ancestral shrine (iso ekpo) from that hitherto worshiped by the inclusive unit. The paradox of Ibibio marriage involving agnatic kin, which this article demonstrates, is that the initial disruption is ameliorated by new but sacred kinship bonds arising from the marriage which reintegrate these lineages as exogamous units at different structural levels.